Effect of egg weight on hatchability, growth and survival rate in japanese quail - Tamer Çağlayan; Şeref İnal (Eurasian Journal of Veterinary Sciences)
This study was carried out to investigate the effects of hatching egg weight on hatchability, growth and survival rate in Japanese Quail. In this investigation, 2147 eggs were obtained from 8-10-weeks old quails that were reared at the Veterinary Faculty Farm of Selçuk University, Turkey and used as the material. Eggs were classified as less than 10 g, 10-11 g, 11-12 g, 12-13 g, 13-14 g, 14-15 g and greater than 15 g. When different egg weight groups were compared on hatchability of total eggs and apparent fertility, there was a statistically important difference (P<